Assessment of Urinary Level of Neutrophil Gelatinaseassociated Lipocalin (NAGL) in Children with Renal Scar Due to Vesicoureteral Reflux (Iranian Journal of Kidney Diseases, 2023)
Introduction. Renal scarring is a serious complications of urinary tract infection and vesicoureteral reflux (VUR). The dimercaptosuccinic acid (DMSA) scan is the gold standard method for diagnosing renal scars but is an expensive procedure that risks ionizing materials and is not available to everyone. Neutrophil gelatinase-associated lipocalin (NGAL) increases following inflammation, infection, and acute kidney injury in the urine. The aim of this study was to evaluate the urinary level of NGAL and determine its diagnostic value in renal scarring. Methods. Patients aged 3 to 60 months with pyelonephritis were included in this study. Voiding cystourethrography (VCUG) was performed in the presence of hydronephrosis on ultrasonography. Children with VUR underwent DMSA scans six months after successful treatment of pyelonephritis., Patients were divided into two groups based on the result of DMSA scan: those with and those without renal scars. Levels of urinary NGAL were measured in both groups. Results. Ninety-two children with VUR (grades 2 to 5) were studied, of whom 40 had renal scars and 52 did not. The urinary level of NGAL at the cutoff point of 284 ng/dL had 70% sensitivity and 100% specificity for the detection of renal scars and was higher in patients with renal scars. (P < .05). Conclusion. The urinary level of NGAL is considerably higher in children with renal scarring. It is not a good test for screening and early diagnosis due to its low sensitivity, although it can identify renal scars caused by VUR with high specificity.  DOI: 10.52547/ijkd.6951